2016
DOI: 10.1103/physrevb.93.134510
|View full text |Cite
|
Sign up to set email alerts
|

Detailed magnetic and structural analysis mapping a robust magneticC4dome inSr1xNaxFe2

Abstract: The recently discovered C4 tetragonal magnetic phase in hole-doped members of the iron-based superconductors provides new insights into the origin of unconventional superconductivity. Previously observed in Ba1-xAxFe2As2 (with A = K, Na), the C4 magnetic phase exists within the well studied C2 spin-density wave (SDW) dome, arising just before the complete suppression of antiferromagnetic (AFM) order but after the onset of superconductivity. Here, we present detailed x-ray and neutron diffraction studies of Sr1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 44 publications
9
50
1
Order By: Relevance
“…12,20,30,31 In these reports we characterized the C 4 phase by an abrupt first order re-entrance at temperatures T < T N to the tetragonal I4/mmm structure from within the well known antiferromagnetically ordered orthorhombic F mmm structure. This structural transition is coupled to a magnetic transition where the previously in-plane Fe-site moments rotate to be co-linear to the c-axis forming a double-Q magnetic structure with P C 4 2 /ncm magnetic space group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…12,20,30,31 In these reports we characterized the C 4 phase by an abrupt first order re-entrance at temperatures T < T N to the tetragonal I4/mmm structure from within the well known antiferromagnetically ordered orthorhombic F mmm structure. This structural transition is coupled to a magnetic transition where the previously in-plane Fe-site moments rotate to be co-linear to the c-axis forming a double-Q magnetic structure with P C 4 2 /ncm magnetic space group.…”
Section: Resultsmentioning
confidence: 99%
“…20 In Sr 1−x Na x Fe 2 As 2 the C 4 phase was found to occur in a small range of As-Fe-As bond angles where the FeAs 4 approached perfect tetrahedra. We suggested that the return locally to a higher symmetry in the Fe 2 As 2 layers might create an electronic instability which contributes to the recovery of magnetic degeneracy and a consequent return to C 4 symmetry.…”
Section: Internal Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…So far three compounds have shown this reentrant tetragonal phase: Ba 1−x Na x Fe 2 As 2 [292], Ba 1−x K x Fe 2 As 2 [293], and Sr 1−x Na x Fe 2 As 2 [294]. Ba 1−x Na x Fe 2 As 2 shows a C 4 phase coexistent with the orthorhombic one just at the antiferromagnetic transition suppression for a small range of doping [292], while this tetragonal region is fully inside the C 2 one in Sr 1−x Na x Fe 2 As 2 [294]. The tetragonal phase in Ba 1−x K x Fe 2 As 2 is also at the magnetic transition but, differently to the other two cases, it is also reentrant as a function of temperature, being suppressed as the superconductivity sets in [293].…”
Section: B Magnetic Softness In Doped Compoundsmentioning
confidence: 99%